Engineering of TiO2 or ZnO—Graphene Oxide Nanoheterojunctions for Hybrid Solar Cells Devices - Duarte Carreira; Paulo A. Ribeiro; Maria Raposo; Susana Sério (Photonics, 2021)
It is currently of huge importance to find alternatives to fossil fuels to produce clean energy and to ensure the energy demands of modern society. In the present work, two types of hybrid solar cell devices were developed and characterized. The photoactive layers of the hybrid heterojunctions comprise poly (allylamine chloride) (PAH) and graphene oxide (GO) and TiO2 or ZnO films, which were deposited using the layer-by-layer technique and DC-reactive magnetron sputtering, respectively, onto fluorine-doped tin oxide (FTO)-coated glass substrates. Scanning electron microscopy evidenced a homogeneous inorganic layer, the surface morphology of which was dependent on the number of organic bilayers. The electrical characterization pointed out that FTO/(PAH/GO)50/TiO2/Al, FTO/(PAH/GO)30/ZnO/Al, and FTO/(PAH/GO)50/ZnO/Al architectures were the only ones to exhibit a diode behavior, and the last one experienced a decrease in current in a low-humidity environment. The (PAH/GO)20 impedance spectroscopy study further revealed the typical impedance of a parallel RC circuit for a dry environment, whereas in a humid environment, it approached the impedance of a series of three parallel RC circuits, indicating that water and oxygen contribute to other conduction processes. Finally, the achieved devices should be encapsulated to work successfully as solar cells.